Securing the wireless internet. - Gupta, V.
Internet-enabled wireless devices continue to proliferate and are expected to surpass traditional Internet clients in the near future. This has opened up exciting new opportunities in the mobile e-commerce market. However, data security and privacy remain major concerns in the current generation of "wireless Web" offerings. All such offerings today use a security architecture that lacks end-to-end security. This unfortunate choice is driven by perceived inadequacies of standard Internet security protocols like SSL on less capable CPUs and low-bandwidth wireless links. This article presents our experiences in implementing and using standard security mechanisms and protocols on small wireless devices. We have created new classes for the Java 2 Micro-Edition platform that offer fundamental cryptographic operations such as message digests and ciphers as well as higher level security protocols like SSL. Our results show that SSL is a practical solution for ensuring end-to-end security of wireless Internet transactions even within today's technological constraints
Keywords: Internet security protocols; Internet-enabled wireless devices; Java 2 Micro-Edition platform; SSL; Ciphers; Cryptographic operations; Data privacy; Data security; End-to-end security; Message digests; Mobile e-commerce market; Security architecture; Small wireless devices; Wireless Internet transactions